Pubertal timing in children with Silver Russell syndrome compared to those born small for gestational age - Patti, Giuseppa; Malerba, Federica; Calevo, Maria Grazia; Schiavone, Maurizio; Scaglione, Marco; Casalini, Emilio; Russo, Silvia; Fava, Daniela; Bassi, Marta; Napoli, Flavia; Allegri, Anna Elsa Maria; D’Annunzio, Giuseppe; et al. (Frontiers in Endocrinology, 2022)
Context Data on pubertal timing in Silver Russell syndrome (SRS) are limited. Design and methods Retrospective observational study including twenty-three SRS patients [11p15 loss of methylation, (11p15 LOM, n=10) and maternal uniparental disomy of chromosome 7 (mUPD7, n=13)] and 21 small for gestational age (SGA). Clinical (thelarche in females; testis volume ≥ 4 ml in males; pubarche), BMI SD trend from the age of 5 to 9 years to the time of puberty, biochemical parameters of puberty onset [Luteinizing hormone (LH), 17-β-estradiol, testosterone], and bone age progression were evaluated Results Pubertal onset and pubarche occurred significantly earlier in children with SRS than in SGA (p 0.03 and p 0.001, respectively) and clinical signs of puberty onset occurred earlier in mUPD7 than in 11p15LOM group (p 0.003). Five SRS children experienced central precocious puberty and LH, 17-β-estradiol, testosterone were detected earlier in SRS than in SGA (p 0.01; p 0.0001). Bone age delay in SRS children was followed by rapid advancement; the delta between bone age and chronological age in SRS group became significantly higher than in SGA group at the age of 9-11 years (p 0.007). 11p15LOM patients were underweight at the age of 5 years and showed a progressive normalization of BMI that was significantly higher than in mUPD7 (p 0.04) and SGA groups (p 0.03) at puberty onset. Conclusion Timing of puberty is affected in SRS and occurred earlier in mUPD7 compared to 11p15LOM. The impact of early puberty on adult height and metabolic status deserves long-term evaluation.